1998
DOI: 10.1038/sj.jhh.1000592
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and gender on ambulatory blood pressure and heart rate

Abstract: In a large group of young (n = 194) and elderly (n = 148) healthy subjects, we explored the relationship between ambulatory blood pressure (BP) levels, within-subject BP variability, and age in men and women. The questions asked were: Do elderly subjects display higher BP levels and variability compared to a young group? Are there gender differences in BP level and variability? Are these gender differences similar in the young and the elderly subjects? Do age or gender influence BP in a similar way during waki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…Using time-domain analysis of the deviation in ABP over a 24-hour period, it has been reported that the ABP variability is increased with aging [12,18] as well as in patho-physiological conditions such as hypertension [39]. Further, a positive relationship between ambulatory blood pressure variability and DBP has recently been demonstrated in elderly individuals [12], providing evidence of dysregulation during relatively benign activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using time-domain analysis of the deviation in ABP over a 24-hour period, it has been reported that the ABP variability is increased with aging [12,18] as well as in patho-physiological conditions such as hypertension [39]. Further, a positive relationship between ambulatory blood pressure variability and DBP has recently been demonstrated in elderly individuals [12], providing evidence of dysregulation during relatively benign activities.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a positive relationship between ambulatory blood pressure variability and DBP has recently been demonstrated in elderly individuals [12], providing evidence of dysregulation during relatively benign activities. Under these circumstances, the development of increased ABP variability has been implicated as a potential cause for end organ damage [12,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of hypertension is higher in men than in women until approximately age 65, after which the prevalence becomes higher in women (81.2 vs. 73.4% in ≥ 75-year-olds) [10]. This is accompanied by greater BP variability on ambulatory 24 h BP monitoring in elderly women than men, which conveys a higher risk of end-organ damage [11]. The higher relative prevalence of hypertension in elderly women may be partially related to premature death of hypertensive males prior to the age of 75 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Adult studies have assessed the variability of both systolic and diastolic blood pressure using measures such as the standard deviation of the daytime mean, 4,5,15 the standard deviation of the night time mean, 5,14 the coefficient of variation (estimated as the standard deviation divided by 100 times the mean blood pressure), 5 the difference between the average value in the top 5% of readings from the overall average for the individual, 4 intermittent standard deviations 6 and the sleep/awake ratio. 16 We used the standard deviation of the 24-h blood pressure monitoring values as a measure of the 24-h variability, which shows the spread of an individuals blood pressure readings taken over a 24-h period.…”
Section: Discussionmentioning
confidence: 99%